2016
DOI: 10.1108/cb-08-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

E-resources: use and search strategies adopted by users of Dr Y.S. Parmar University of Horticulture and Forestry

Abstract: Purpose – The purpose of this paper is to identify the most popular places, gadgets, searching tools and techniques adopted by users of Dr Y.S. Parmar University of Horticulture and Forestry (DYSPUH & F), Nauni, Solan, Himachal Pradesh, while searching electronic information resources (EIRs). Design/methodology/approach – A survey was conducted with the help of a structured questionnaire used as a data collection tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
4
1
Order By: Relevance
“…It has been observed that e-journals (75 %) and e-books (48 %) are the most preferred e-resources similar to the findings of Francis 6 , Kandpal, et al, 10 Bhat & Ganaie 14 and contrary to the findings of Kumar. 15 It is worthy to mention that national and international…”
Section: Discussioncontrasting
confidence: 56%
“…It has been observed that e-journals (75 %) and e-books (48 %) are the most preferred e-resources similar to the findings of Francis 6 , Kandpal, et al, 10 Bhat & Ganaie 14 and contrary to the findings of Kumar. 15 It is worthy to mention that national and international…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to the existing literature on e-resources, the present study records the perception of management students belonging to different disciplines such as marketing, finance, human resources, operations, economics and information technology. According to the reviewed literature, very few studies in the area of e-resources have reported the perspective of postgraduate students (Wu and Chen, 2012; Adeniyi Aderibigbe and Adebimpe Ajiboye, 2013; Makori, 2015; Bhat and Ganaie, 2016), and only a handful of studies have examined the usage pattern of e-resources of management students (Kumar and Kumar, 2010; Swain, 2010). However, none of these studies have reported and compared the responses of management students on the bases of their disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents-wise investigation reveals that, thus far, the usefulness of e-resources has been studied from the perspective of undergraduate students, librarians, research scholars, faculty members and administrative staff (Swain and Panda, 2009; Kumar and Kumar, 2010; Madhusudhan, 2010; Olle and Borrego, 2010; Tahir et al , 2010; Sharma et al , 2011; Zhang et al , 2011; Jeong Kim et al , 2012; Zha et al , 2013). However, only a limited number of studies recorded the responses of postgraduate students (Wu and Chen, 2012; Adeniyi Aderibigbe and Adebimpe Ajiboye, 2013; Makori, 2015; Bhat and Ganaie, 2016), while at the same time, very few studies surveyed management students and recorded their responses (Kumar and Kumar, 2010; Swain, 2010). Among these, Kumar and Kumar (2010) interviewed students and faculty members from the engineering, medical and management disciplines in Bangalore city, while Swain (2010) recorded the perspectives of students from business schools in Orissa, as far as their awareness, interest level, frequency of use and problems faced while using e-resources are concerned.…”
Section: Review Of Literaturementioning
confidence: 99%
“…That is why many institutions formulate and implement various marketing strategies and tactics to generate awareness about e-resources among students (Harlow and Hill, 2020). Due to lack of awareness and proper training, the students prefer to use search engines for finding the relevant information (Anaraki and Babalhavaeji, 2013; Bhat and Ganaie, 2016; Vasilyeva and Vasilyeva, 2019). Influencers like faculty, library staff, etc.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…In the event of low awareness, it becomes a challenge for institutes to justify the price of e-resources against usage (Harlow and Hill, 2020). Moreover, students start referring to search engines more than subscribed e-resources to satiate informational needs (Anaraki and Babalhavaeji, 2013;Bhat and Ganaie, 2016). Students also lack confidence to use e-resources in the absence of awareness (Deng, 2010).…”
Section: Awarenessmentioning
confidence: 99%